Associations between personal goals, classroom goals and study habits - Wee, Marie Elizabeth Kim Hui (Nanyang Technological University, 2023)
Usage of metacognitive strategies have commonly been suggested to be important for attaining academic success (Ohtani & Hisasaka, 2018; Zulkiply, 2006) as well as for becoming an effective lifelong learner (Cornford, 1999). However, it has been suggested that students do not regularly employ metacognitive strategies (Bandura, 1993). Personal goal orientation and classroom structure are factors that have often been suggested to influence metacognitive strategy usage. However, while much of past research have investigated their independent influence on metacognitive strategy usage, there are limited studies that investigated their joint influence on metacognitive strategy usage in Science education. Therefore, this study examines how personal goal orientation and classroom structure might independently and jointly influence one’s metacognitive strategy usage in Science education. To investigate this, this study recruited 30 Chemistry-taking Singapore students to complete a series of online questionnaires. Results reveal a significant positive correlation with metacognitive strategy usage for mastery goal orientation, performance-approach goal orientation, and mastery classroom structure. However, results also notes non-significant interactions between mastery goal orientation and classroom structures, and between performance-approach goal orientation and classroom structures. These findings further add to the literature on metacognitive strategy usage and could also have implications on instructional practices in schools.